Comparative Assessment of Co2 Emission Factors Estimated Using Stack Flue Gas Measurement Data for Two Types of Brick Kiln: A Case Study in Phu Tho Province, Vietnam - Nguyen, Duc Luong; Nguyen, Thanh Trung; Nguyen, Duy Thai; Nguyen, Duy Dong (Review of Environment and Earth Sciences, 2015)
In Vietnam, the brick production sector is one of the construction material production sectors that has large emission of CO2 – the major greenhouse gas, since it consumes a large amount of fossil fuels. This research aims at preliminarily estimating the CO2 emission factors for two major kiln technologies used in brick production sector in Vietnam, namely tunnel and vertical shaft brick kiln (VSBK). For this purpose, field measurement of CO2 concentration in stack flue gases of two brick factories in Phu Tho province – one of the largest brick production areas in the North of Vietnam were conducted. The results of data analysis have shown that the tunnel kiln has higher CO2 emission factors compared to those of VSBK. The lower specific energy consumption and lower heat losses are the major causes for lower CO2 emission factors of VSBK.